Knowledge, Attitude and Practice Regarding Personal Protective Equipment During COVID–19 Pandemic Among Healthcare Workers in Hetauda - Bhattarai, Susmita; Pradhan, Srijana (Nepal Journal of Health Sciences, 2021)
Introduction: Personal protective equipment (PPE) is one of the effective measures to protect health care workers while caring confirmed or suspected patients with COVID-19.Objective: To assess the knowledge, attitude, and practice regarding the use of PPE among healthcare workers (HCWs) in Hetauda during COVID-19 pandemic.Methods: A descriptive cross-sectional study was conducted among 138 HCWs from three hospitals in Hetauda: Hetauda Hospital, Makwanpur Sahakari hospital and Hetauda Orthopedic Hospital between December 2020 and January 2021 for two weeks. A validated self-administered questionnaire, Likert scale and Observational checklist were used for data collection. The simple descriptive statistics (percentage, mean) and inferential statistics (Chi-square test) were used for the data analysis.Results: The findings of the study showed that the mean age of the respondents was 26.54 years. Half of the total respondents 70 (50.7%) had adequate knowledge, half 69 (50%) had positive attitude and more than half of the respondents had poor practice 60 (60%) regarding the use of PPE during COVID-19 pandemic. There was significant association of knowledge regarding the use of PPE with training, continue education, profession and attitude at p